Determinants of acceptability of schistosomiasis mass drug administration among primary school children in Busega District, Northwestern Tanzania - Irene Yunzu Edward; Patricia Maritim; Choolwe Jacobs; Adam Silumbwe; Hussein Mohamed; Joseph Mumba Zulu; Hikabasa Halwiindi (PLoS ONE, 2025)
Background Schistosomiasis is endemic in Tanzania, with a prevalence ranging between 12.7% to 87.6%. Mass drug administration (MDA) with praziquantel is the main recommended choice of preventive treatment for the disease. Low treatment coverage rates (46.6%) in Busega District, Northwestern Tanzania which are far less than the recommended effective coverage rates of ≥ 75% could indicate low acceptability and poor uptake of MDA. This study sought to establish factors associated with acceptability of schistosomiasis mass drug administration among primary school children in Busega District. Methods A cross-sectional study was conducted among primary school children, randomly selected from six primary schools between 6th March and 29th May 2023. A validated generic questionnaire guided by the Theoretical Framework of Acceptability was used for data collection. The outcome of the study was acceptability of MDA, and the explanatory variables were socio-demographic factors and the seven constructs of the framework such as perceived moral about taking praziquantel, understanding of intervention purpose and affective attitude. Descriptive statistics and logistic regression with robust standard errors were conducted to identify factors associated with acceptability of MDA using STATA version 15. Results The study sample comprised 615 primary school children, 60.16% girls and 39.84% boys. Age distribution ranged from 10 to 17 years with a median age of 13 years. About 55.28% were found to have high acceptability of MDA. Factors significantly associated with acceptability of MDA were; perceived effectiveness (AOR = 2.52; 95%CI = 1.31–4.85; p-value = 0.006), understanding of intervention purpose (AOR = 5.51; 95%CI = 3.16–9.59; p-value<0.0001), self-efficacy (AOR = 2.04; 95% CI = 1.08–3.85; p-value = 0.029), affective attitude (AOR = 5.10; 95% CI = 2.77–9.59; p-value<0.0001), and gender (AOR = 0.59; 95% CI = 0.38–0.94; p-value = 0.027). Conclusion Slightly more than half of primary school children recorded high acceptability of MDA. However, perceived effectiveness, understanding of intervention purpose, self-efficacy, affective attitude, and gender strongly influence acceptability. This underscores the need for tailored, gender-sensitive community sensitization efforts regarding the benefits of MDA. Targeted educational campaigns and peer-led initiatives should be prioritized to increase awareness and acceptance, ultimately improving the effectiveness of the MDA program.